The Duty of Women to Preserve Family Found in Fay Weldon's Weekend - Latupeirissa, Kezia Ivanna Maybella; Zebua, Gifford Alvenius; Barus, Cicilia Clara Angel Br; Sijabat, Lulu Ribka Roito; Girsang, Martina (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study examines the importance of women in preserving family structures, as represented in Fay Weldon's short story Weekend, with a focus on traditional gender roles. Using feminist literary criticism as the primary analytical framework, the study focuses on how the narrative depicts gender dynamics within the family. Marta plays the dual position of working woman and homemaker, combining agentic and communal features while fulfilling her responsibilities as a wife and mother. Martin, her spouse, follows traditional masculine duties as provider and decision-maker, but with less emotional involvement. The study also looks at ancillary characters like Colin, Janet, and Katie, who reflect different ideas on gender roles, from conventional homemaking to liberal feminism. The study uses a qualitative descriptive method to relate the story's characters and themes to larger feminist theories, demonstrating the interaction of gender roles, societal expectations, and family dynamics. This analysis helps to a better understanding of how literature can be used to explore and critique gender relations, as well as provide insights into changing social norms.